Asupan natrium dan kalium berhubungan dengan frekuensi kekambuhan sindrom dispepsia fungsional - Hervina Dwijayanti; Neneng Ratnasari; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2008)
Background: A high-salt diet is known to cause gastritis, has been associated with a high risk of atrophic gastritis, and is considered a gastric tumor promoter. Excessive NaCl intake enhances Helicobacter pylori colonization in mice and in humans and that chronic salt intake may exacerbate gastritis by increasing Helicobacter pylori colonization. Furthermore, elevated salt intake may potentiate Helicobacter pylori-associated carcinogenesis by inducing proliferation, pit cell hyperplasia, and glandular atrophy.Objective: The aim of this research was to describe the correlation between sodium and potassium intake and relapse frequent functional dyspepsia syndrome in Sardjito Hospital Yogyakarta.Method: This was an observational research with cross sectional design. The subjects of this research were 32 course care patients in Sardjito Hospital Yogyakarta on November 2006–Januari 2007 who met the inclusion criteria. Those were who diagnosed as functional dyspepsia, with or without Helicobacter pylori infection, and above eighteen years old. Data were collected by interviewing and gathered from medical record, then analyzed using Rank-Spearman test.Results: The average of the relapse frequent of dyspepsia syndrome in Sardjito Hospital was 14.38 ±2.93, with the minimum score was 4 and the maximum score was 32. The result showed that sodium intake gave a positive relation and significant for relapse frequent of dyspepsia syndrome (p<0.05). The potassium intake gave a negative relation and significant for relapse frequent of dyspepsia syndrome (p<0.05).Conclusion : There was a positive and significant correlation between sodium intake and relapse frequent of dyspepsia syndrome, but there was a negative and significant correlation between potassium intake and relapse frequent of dyspepsia syndrome.